Unraveling the role of C1GALT1 in abnormal glycosylation and colorectal cancer progression - Tian, Hong; Yu, Jia-Li; Chu, Xiaoli; Guan, Qi; Liu, Juan; Liu, Ying (Frontiers in Oncology, 2024)
C1GALT1 plays a pivotal role in colorectal cancer (CRC) development and progression through its involvement in various molecular mechanisms. This enzyme is central to the O-glycosylation process, producing tumor-associated carbohydrate antigens (TACA) like Tn and sTn, which are linked to cancer metastasis and poor prognosis. The interaction between C1GALT1 and core 3 synthase is crucial for the synthesis of core 3 O-glycans, essential for gastrointestinal health and mucosal barrier integrity. Aberrations in this pathway can lead to CRC development. Furthermore, C1GALT1's function is significantly influenced by its molecular chaperone, Cosmc, which is necessary for the proper folding of T-synthase. Dysregulation in this complex interaction contributes to abnormal O-glycan regulation, facilitating cancer progression. Moreover, C1GALT1 affects downstream signaling pathways and cellular behaviors, such as the epithelial-mesenchymal transition (EMT), by modifying O-glycans on key receptors like FGFR2, enhancing cancer cell invasiveness and metastatic potential. Additionally, the enzyme's relationship with MUC1, a mucin protein with abnormal glycosylation in CRC, highlights its role in cancer cell immune evasion and metastasis. Given these insights, targeting C1GALT1 presents a promising therapeutic strategy for CRC, necessitating further research to develop targeted inhibitors or activators. Future efforts should also explore C1GALT1's potential as a biomarker for early diagnosis, prognosis, and treatment response monitoring in CRC, alongside investigating combination therapies to improve patient outcomes.